Kontroversi Penerapan Hukum Pidana Internasional Secara Retroaktif Terhadap Pelaku Kejahatan Perang Di Palestina - Pranata, Ilyas Patu (PSHPM Untag Semarang, 2026)
The retroactive application of international criminal law to perpetrators of war crimes in Palestine has sparked deep debates regarding legality, legitimacy, and its impact on the international legal system. This study aims to analyze the juridical and political implications of such an application in the context of human rights protection, achieving justice for victims, and the dynamics of international relations between states. The principle of non-retroactivity in international criminal law, which is normatively recognized, is often confronted with exceptional circumstances, such as serious violations of international humanitarian law. Through a juridical-normative approach and literature study, this research evaluates the extent to which the legitimacy of the International Criminal Court (ICC) is accepted by the global community when its jurisdiction is considered to exceed the specified time limits. The findings indicate that retroactive application can be justified morally and legally in certain situations, although it has the potential to trigger geopolitical tensions, particularly from countries that have not ratified the Rome Statute. This study recommends the need for a stronger international consensus to ensure the accountability of war crime perpetrators without compromising global political stability.